A molecular evidence for the presence of methylobacterial-type Fe siderophore receptor in Celosia cristata - A. Gholizadeh; B.B. Kohnehrouz (Plant, Soil and Environment, 2010)
The presence of efficient iron-uptake bacteria was predicted to be localized as endosymbionts within the leaves of Celosia cristata, a well known iron-rich plant. On the other hand, the symbiotic methylobacterium having a distinctive pink pigmentation was suggested to be more likely in the leaves of pink-colored plants. These considerations were experimented by priming a cDNA fragment containing methylobacterial-type Fe siderophore receptor domain from Celosia leaf cDNA population. Since no detectable homologue was found in plant species sequenced to date, the presence of a Fe-efficient methylobacterium endosymbiosis was reliably predicted in Celosia plant. This is the first report that may lead to the way for future studies on molecular interactions between high iron content pink-colored plants and iron-efficient pink-pigmented bacteria. Corresponding cDNA sequence was submitted to EMBL databases under accession number FM955594.